Asymmetric Supramolecular Organocatalysis: A Complementary Upgrade to Organocatalysis. Issue 37 (21st June 2017) - Anebouselvy, Kengadarane; Shruthi, Kodambahalli S.; Ramachary, Dhevalapally B.
Abstract : The recent past has witnessed tremendous growth in the field of asymmetric synthesis through "asymmetric supramolecular organocatalysis (ASO)". ASO emerges from many interactions between substrates and catalysts: namely substrate–catalyst, catalyst–catalyst and substrate–substrate interactions. As a result, ASO has come to be the fourth pillar of asymmetric catalysis. This review summarizes recent advances in the high‐yielding asymmetric synthesis of chiral compounds from functionally rich substrates with the aid of combinations of two or more organocatalysts working synergistically through relatively stable pre‐transition states. ASO not only assists in product formation from highly functionalized substrates with high rate/selectivity, but also sheds some light on understanding of the fundamental aspects of the pre‐transition state structures. Abstract : Asymmetric supramolecular organocatalysis emerges from many interactions between substrates and catalysts: namely, substrate–catalyst, catalyst–catalyst and substrate–substrate interactions. Here the importance and applications of these interactions in governing both the reactivity and the selectivity of asymmetric organocatalytic reactions as a result of stable pre‐transition states are shown.